2022
DOI: 10.1002/anie.202214449
|View full text |Cite
|
Sign up to set email alerts
|

Large‐area Free‐standing Metalloporphyrin‐based Covalent Organic Framework Films by Liquid‐air Interfacial Polymerization for Oxygen Electrocatalysis

Abstract: Synthesizing large‐area free‐standing covalent organic framework (COF) films is of vital importance for their applications but is still a big challenge. Herein, we reported the synthesis of large metalloporphyrin‐based COF films and their applications for oxygen electrocatalysis. The reaction of meso‐benzohydrazide‐substituted metal porphyrins with tris‐aldehyde linkers afforded free‐standing COF films at the liquid‐air interface. These films can be scaled up to 3000 cm2 area and display great mechanical stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…Notably, very recent progress has shown that metalorganic molecule-based framework catalysts are highly active in bifunctional electrocatalytic oxygen reduction and evolution reactions. [20][21][22] In the present study, a nitrogen-doped NiCoO x nanosheet array catalyst with an ultrathin thickness of 1-3 nm has been developed. The prepared electrocatalyst has a large exposed surface area, an abundance of exposed edge sites, and a firm electrical connection with a conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, very recent progress has shown that metalorganic molecule-based framework catalysts are highly active in bifunctional electrocatalytic oxygen reduction and evolution reactions. [20][21][22] In the present study, a nitrogen-doped NiCoO x nanosheet array catalyst with an ultrathin thickness of 1-3 nm has been developed. The prepared electrocatalyst has a large exposed surface area, an abundance of exposed edge sites, and a firm electrical connection with a conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, very recent progress has shown that metal–organic molecule-based framework catalysts are highly active in bifunctional electrocatalytic oxygen reduction and evolution reactions. 20–22…”
Section: Introductionmentioning
confidence: 99%
“…22 Co-porphyrin and Co-corrole based molecular catalysts that combine metal redox property with π-conjugation of ligands showed strong OER activity. [23][24][25][26][27] Cobalt hydroxides (Co(OH) 2 ) with their abundance and environmental friendliness provided an opportunity to fabricate cost-effective OER catalysts. [28][29][30][31][32] However, the fully occupied t 2g orbitals of the MO 6 centre in Co(OH) 2 resulted in a low electron transfer conductivity and contributed to reduced OER activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive efforts have been devoted to synthesizing noble metal-free electrodes for highly efficient oxygen electrocatalysis. 17–25 Cost-effective bifunctional catalytic electrocatalysts that can accelerate both the ORR and OER have sprung up for high-performance ZABs. 26–31…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive efforts have been devoted to synthesizing noble metal-free electrodes for highly efficient oxygen electrocatalysis. [17][18][19][20][21][22][23][24][25] Cost-effective bifunctional catalytic electrocatalysts that can accelerate both the ORR and OER have sprung up for high-performance ZABs. [26][27][28][29][30][31] Transition metal (TM) compounds embedded in nitrogen (N)-doped carbon electrocatalysts have been screened for efficient oxygen reduction.…”
Section: Introductionmentioning
confidence: 99%